Transformerless DC/AC Converter For Grid-Connected PV Power Generation System - Azri, Maaspaliza; Abdul Rahim, Nasruddin; Mohamad Elias, Mohamad Fathi (SPRINGER, 2014)

(untitled)
Transformerless photovoltaic (PV) systems have two shortcomings:low voltage not fulfilling load requirement and ground-leakage current flowing through parasitic capacitance between the PV panel and ground.Therefore,a DC/AC converter—a single-phase bipolar sinusoidal pulse width modulation (SPWM) H-Bridge power inverter configuration with a DC/DC high-gain conversion-boosting (CDBoost)stage—is proposed.Its conversion ratio was compared with a conventional converter’s.It provides a high conversion ratio of the PV voltage before the DC is converted into AC for the load.The bipolar SPWM modulation technique is proposed for lower ground-leakage current,and the effectiveness of the proposed modulation technique was compared with the unipolar SPWM technique.The effect of unbalanced filter inductance and of parasitic capacitance on the combined CD-Boost bipolar SPWM H-Bridge converter system was investigated. Simulation and experiment results verified the proposed converter’s feasibility in addressing issues of transformerless DC/AC converters in grid-connected PV systems.